2019
DOI: 10.1371/journal.pone.0210608
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic antitumor effects of 9.2.27-PE38KDEL and ABT-737 in primary and metastatic brain tumors

Abstract: Standard treatment, unfortunately, yields a poor prognosis for patients with primary or metastatic cancers in the central nervous system, indicating a necessity for novel therapeutic agents. Immunotoxins (ITs) are a class of promising therapeutic candidates produced by fusing antibody fragments with toxin moieties. In this study, we investigated if inherent resistance to IT cytotoxicity can be overcome by rational combination with pro-apoptotic enhancers. Therefore, we combined ITs (9.2.27-PE38KDEL or Mel-14-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Most recently, ABT-737 and two other BH3 mimetics were tested in combination with a chondroitin sulfate proteoglycan 4 (CSPG4)-targeting immunotoxin in patient-derived melanoma, glioblastoma, and breast cancer cell lines and demonstrated significant synergy. The same study further confirmed the efficacy of the combination in in vivo nude mice studies of glioblastoma and metastatic cerebral melanoma [ 45 ].…”
Section: Immunotoxin Processing and Trafficking (Step 2)mentioning
confidence: 64%
“…Most recently, ABT-737 and two other BH3 mimetics were tested in combination with a chondroitin sulfate proteoglycan 4 (CSPG4)-targeting immunotoxin in patient-derived melanoma, glioblastoma, and breast cancer cell lines and demonstrated significant synergy. The same study further confirmed the efficacy of the combination in in vivo nude mice studies of glioblastoma and metastatic cerebral melanoma [ 45 ].…”
Section: Immunotoxin Processing and Trafficking (Step 2)mentioning
confidence: 64%
“…ABT drugs have been tested on patient glioblastomas in culture [43]; but these molecules are generally considered to be too large to cross the blood-brain barrier (BBB) [44]. Yet, the BBB becomes more porous with age even to such large proteins as albumin [45][46][47].…”
Section: Resultsmentioning
confidence: 99%
“…A number of BH3 mimetics have been established, e.g., ABT-737, ABT-263, A-1155463, and S63845, as well as ABT-199 (Venetoclax), which has been approved for treatment of refractory chronic lymphocytic leukemia [38,108,109]. Although BH3 mimetics were less effective in melanoma cells as a single therapy, they revealed synergistic effects in combinations, e.g., with immunotoxins or the proteasome inhibitor bortezomib [42,110]. Due to the in vitro data, one might also expect good combination effects for BH3 mimetics and TRAIL in melanoma cells, as has been previously shown in glioma cells [111].…”
Section: Discussionmentioning
confidence: 99%